2001
DOI: 10.1074/jbc.m011252200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Sperm-specific Proteins That Interact with A-kinase Anchoring Proteins in a Manner Similar to the Type II Regulatory Subunit of PKA

Abstract: The cAMP-dependent protein kinase (PKA) is targeted to specific subcellular compartments through its interaction with A-kinase anchoring proteins (AKAPs). AKAPs contain an amphipathic helix domain that binds to the type II regulatory subunit of PKA (RII). Synthetic peptides containing this amphipathic helix domain bind to RII with high affinity and competitively inhibit the binding of PKA with AKAPs. Addition of these anchoring inhibitor peptides to spermatozoa inhibits motility (Vijayaraghavan, S., Goueli, S.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
122
0
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 107 publications
(126 citation statements)
references
References 42 publications
1
122
0
3
Order By: Relevance
“…For some of these, the available information about these proteins suggests that they are axonemal proteins. For example, several sperm-or testisspecific proteins were identified, including an AKAP-associated sperm protein (30), SPAG 6, and Sp17. SPAG6 demonstrates 85% similarity to the Chlamydomonas protein pf16, which localizes to the flagellar central pair microtubules (31), whereas Sp17 has been localized to both the acrosomal region and throughout the sperm tail.…”
Section: Discussionmentioning
confidence: 99%
“…For some of these, the available information about these proteins suggests that they are axonemal proteins. For example, several sperm-or testisspecific proteins were identified, including an AKAP-associated sperm protein (30), SPAG 6, and Sp17. SPAG6 demonstrates 85% similarity to the Chlamydomonas protein pf16, which localizes to the flagellar central pair microtubules (31), whereas Sp17 has been localized to both the acrosomal region and throughout the sperm tail.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its structural support role, the FS may play a more direct role in the regulation of flagellar motility because a growing number of proteins involved in motility signalling pathways and metabolism have been localised to the FS (Carrera et al 1994;Bradley et al 1996;Westhoff and Kamp 1997;Bunch et al 1998;Miki and Eddy 1998;Mori et al 1998;Travis et al 1998;Turner et al 1998Turner et al , 1999Nakamura et al 1999;Fujita et al 2000;Carr et al 2001). It has also been suggested that at least one FS protein may act to protect sperm from oxidative stress, which could interfere with sperm motility or cause DNA damage (Fulcher et al 1995).…”
Section: Fuel Support and More: The Fibrous Sheathmentioning
confidence: 99%
“…This finding suggests that, like other members of the AKAP family, AKAP4 is responsible for tethering several different proteins to a specific subcellular region. In this regard, other proteins have been implicated as being compartmentalised to the flagellum, and specifically to the FS, via interactions with anchoring proteins (Carr et al 2001;Brown et al 2003).…”
Section: Being In the Right Place At The Right Timementioning
confidence: 99%
See 1 more Smart Citation
“…Normal mammalian sperm motility seems to be governed predominantly by the cAMP/PKA pathway and calcium signaling pathway, whereas mechanisms involving heterotrimeric and small G-proteins have also been entailed the regulation of sperm motility. 50 It should be emphasized that cAMP may also act through PKA-independent pathways. Burton et al 51 speculated that cAMP may activate a cyclic-nucleotide-gated ion channel in spermatozoa and/or cAMP-mediated guanine nucleotide exchange factors in testes, providing these ways as alternative pathways for the PKAmediated regulation of flagellar motility.…”
Section: In Vitro Effectmentioning
confidence: 99%